Raising the Stakes: Physician Facility Investments and Provider Agency - Munnich, Elizabeth L.; Richards, Michael R.; Whaley, Christopher M.; Zhao, Xiaoxi (American Economic Review, 2026)
Principal-agent problems often extend beyond what can be directly addressed through conventional incentive arrangements. We examine a context where physicians are likely under-incentivized to minimize total medical costs until their private financial interests align with those of patients. Leveraging novel data on physician ownership of ambulatory surgery centers——that is, same-day facilities——we show that these equity holdings cause a substitution away from higher cost, rival settings that lowers Medicare spending by 10–40 percent per physician. We find no clear evidence of perverse behavior following these investments. Instead, our findings demonstrate how entrepreneurial activity can indirectly limit principal-agent problems and improve efficiency. (JEL D82, D91, G51, I11, I18, L84)